1998
DOI: 10.1093/oxfordjournals.schbul.a033356
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Laterality and Selective Attention: Normal Performance in Patients With Early-Onset Schizophrenia

Abstract: In this study, auditory laterality and selective attention were examined in patients with early-onset schizophrenia using a dichotic listening (DL) test. Deficient performance on this test has repeatedly been found in adult patients with chronic schizophrenia, indicating abnormalities in left hemisphere function. The hypothesis in the present study was that subjects with early-onset schizophrenia manifest deficits in DL test performance similar to adult chronic patients. A group of 19 patients with early-onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 55 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Meta-analysis was conducted on 10 dichotic listening studies that compared patients with schizophrenia to healthy controls (Hatta et al , 1984; Wexler et al , 1991; Carr et al , 1992; Ragland et al , 1992; Seidman et al , 1993; Grosh et al , 1995; Sakuma et al , 1996; Oie et al , 1998; Bruden et al , 1999; Løberg et al , 1999). The right-ear advantage was not significantly decreased in schizophrenia, with significant heterogeneity among studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis was conducted on 10 dichotic listening studies that compared patients with schizophrenia to healthy controls (Hatta et al , 1984; Wexler et al , 1991; Carr et al , 1992; Ragland et al , 1992; Seidman et al , 1993; Grosh et al , 1995; Sakuma et al , 1996; Oie et al , 1998; Bruden et al , 1999; Løberg et al , 1999). The right-ear advantage was not significantly decreased in schizophrenia, with significant heterogeneity among studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A group of Norwegian investigators has demonstrated that adolescents and young adults with ADHD or schizophrenia did not show any impairments in selective attention or auditory laterality on a dichotic listening task. 26 In another study using a covert orientation task, this group demonstrated that adolescents with schizophrenia exhibit abnormal disengagement of attention in comparison to ADD subjects. 27 Other comparisons between schizophrenic and ADD children have been conducted by investigators at UCLA.…”
Section: Other Experimental Paradigmsmentioning
confidence: 95%
“…Subjects with ADD have been used as controls for a number of studies of schizophrenia using other experimental paradigms. A group of Norwegian investigators has demonstrated that adolescents and young adults with ADHD or schizophrenia did not show any impairments in selective attention or auditory laterality on a dichotic listening task 26. In another study using a covert orientation task, this group demonstrated that adolescents with schizophrenia exhibit abnormal disengagement of attention in comparison to ADD subjects 27…”
Section: Experimental Studies Of Attentionmentioning
confidence: 97%
“…It is arguable that abnormal laterality reported on the DL test may be related to hallucinations rather than the disorder per se [Loberg et al, 2004]. For example, normal laterality has been shown in early‐onset schizophrenic patients [Oie et al, 1998] as well as schizophrenic patients in clinical remission [Bruder, 1983]. Auditory hallucinations [Green et al, 1994; Levitan et al, 1999] or positive symptoms [Bruder et al, 1995] have been shown to be associated with a reduced REA.…”
Section: Discussionmentioning
confidence: 99%